Analisis kebutuhan pemustaka pada kegiatan layanan pengembangan koleksi buku Perpustakaan IAIN Batusangkar - Tri Yuliani (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2020)
This study analyzes the needs of users' collections through the development of collections conducted by the Batusangkar IAIN library. This research is a case study conducted using the description method that illustrates the implementation and obstacles faced by the library, there is a collection development analysis activity according to user needs. the benchmarks in this research are study materials or strategies that will be applied for the future by improving the present situation. This study provides findings that activities and evaluations must be carried out on all planning processes with in-depth analysis of the needs of the visitors. This situation causes the librarians to be confused to develop a collection of books so that they cannot determine the type of collection that is needed by the user. More in-depth analysis activities by auditing information and interviews with users are needed for library development.